2009
DOI: 10.1186/cc8027
|View full text |Cite
|
Sign up to set email alerts
|

Brachial artery peak velocity variation to predict fluid responsiveness in mechanically ventilated patients

Abstract: IntroductionAlthough several parameters have been proposed to predict the hemodynamic response to fluid expansion in critically ill patients, most of them are invasive or require the use of special monitoring devices. The aim of this study is to determine whether noninvasive evaluation of respiratory variation of brachial artery peak velocity flow measured using Doppler ultrasound could predict fluid responsiveness in mechanically ventilated patients.MethodsWe conducted a prospective clinical research in a 17-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Although SB and mechanical ventilation have inversed physiological effects on cardiac preload, respiratory changes in SV or surrogates are correlated with VE-induced changes in SV [4]. As previously described [4], the sensitivity of ΔVF and ΔPP in our study was lower than that in mechanically ventilated patients [19, 22]. Nevertheless, the predictive value of ΔPP in mechanically ventilated patients can be altered when tidal volume is low [14].…”
Section: Discussionsupporting
confidence: 51%
“…Although SB and mechanical ventilation have inversed physiological effects on cardiac preload, respiratory changes in SV or surrogates are correlated with VE-induced changes in SV [4]. As previously described [4], the sensitivity of ΔVF and ΔPP in our study was lower than that in mechanically ventilated patients [19, 22]. Nevertheless, the predictive value of ΔPP in mechanically ventilated patients can be altered when tidal volume is low [14].…”
Section: Discussionsupporting
confidence: 51%
“…The reliability of the latter index is likely lower in the ICU patients than in the operating room patients [30] and in case of vasopressors administration [31, 32]. It has even been suggested that the variations of the peak velocity in the carotid [33] or brachial [34] arteries could reflect PPV and detect preload responsiveness.…”
Section: Pulse Pressure and Stroke Volume Variation: Well-establishedmentioning
confidence: 99%
“…Since the introduction of EGDT, the need for placement of a CVC in sepsis has come under increasing scrutiny. Alternative means of monitoring fluid responsiveness and adequacy of resuscitation that do not rely on central venous access RECEIVED: 19 May 2017; FINAL SUBMISSION RECEIVED: 22 August 2017; ACCEPTED: 14 September 2017 have been described (7)(8)(9)(10)(11)(12)(13)(14). The placement of a CVC has also been identified as a barrier to the implementation of EGDT, as it is a time-consuming procedure that cannot always be easily or safely performed in the ED (15,16).…”
Section: Introductionmentioning
confidence: 99%